ANALISIS PENGARUH DUKUNGAN SELEBRITI TERHADAP PEMBELIAN ULANG MELALUI SIKAP TERHADAP MEREK DAN KEPERCAYAAN MEREK SEBAGAI VARIABEL INTERVENING (Studi Pada Erigo Apparel) - Damara Putra, Muhammad Sadam; Idris, Idris (Diponegoro Journal of Management, 2023)
ABSTRACT The phenomenon that has happened to Erigo is that Erigo's sales are still relatively low even though it has been established for 13 years. Intense competition in the fashion industry forces Erigo to think how to increase his sales. One of the ways that Erigo used to increase his sales was by using celebrity endorsements. This study aims to analyze the effect of celebrity endorsement on repurchase intention through brand attitude and brand trust. The population in this study are all Erigo consumers. The sampling technique in this study was using purposive sampling. The samples taken were 125 Erigo consumer respondents who had purchased 2 times in the last two years. The data collection method in this study used a questionnaire. The data analysis method uses structural equation modeling with AMOS software. The results of this study indicate that celebrity endorsement has a positive and significant effect on repurchase intention, celebrity endorsement has a positive and significant effect on brand attitudes, and also celebrity endorsement has positive and significant effect on brand trust. Brand attitude has no effect on repurchase intention, and brand trust has a positive and significant effect on repurchase intention